Mental, neurological, and substance use problems among refugees in primary health care: analysis of the Health Information System in 90 refugee camps - Kane, Jeremy C (BMC Med, 2014)
BACKGROUND: Population-based epidemiological research has established that refugees in low- and middle-income countries (LMIC) are at increased risk for a range of mental, neurological and substance use (MNS) problems. Improved knowledge of rates for MNS problems that are treated in refugee camp primary care settings is needed to identify service gaps and inform resource allocation. This study estimates contact coverage of MNS services in refugee camps by presenting rates of visits to camp primary care centers for treatment of MNS problems utilizing surveillance data from the Health Information System (HIS) of the United Nations High Commissioner for Refugees. METHODS: Data were collected between January 2009 and March 2013 from 90 refugee camps across 15 LMIC. Visits to primary care settings were recorded for seven MNS categories: epilepsy/seizure; alcohol/substance use; mental retardation/intellectual disability; psychotic disorder; emotional disorder; medically unexplained somatic complaint; and other psychological complaint. The proportion of MNS visits attributable to each of the seven categories is presented by country, sex and age group. The data were combined with camp population data to generate rates of MNS visits per 1,000 persons per month, an estimate of contact coverage. RESULTS: Rates of visits for MNS problems ranged widely across countries, from 0.24 per 1,000 persons per month in Zambia to 23.69 in Liberia. Rates of visits for epilepsy were higher than any of the other MNS categories in nine of fifteen countries. The largest proportion of MNS visits overall was attributable to epilepsy/seizure (46.91% male/35.13% female) and psychotic disorders (25.88% male/19.98% female). Among children under five, epilepsy/seizure (82.74% male/82.29% female) also accounted for the largest proportion of MNS visits. CONCLUSIONS: Refugee health systems must be prepared to manage severe neuropsychiatric disorders in addition to mental conditions associated with stress. Relatively low rates of emotional and substance use visits in primary care, compared to high prevalence of such conditions in epidemiological studies suggest that many MNS problems remain unattended by refugee health services. Wide disparity in rates across countries warrants additional investigation into help seeking behaviors of refugees and the capacity of health systems to correctly identify and manage diverse MNS problems.